PERENCANAAN EMBUNG SEMAR KABUPATEN REMBANG - Muchammad Chusni Irfany; Satriyo Pandu Wicaksono; Suripin Suripin; Sri Eko Wahyuni (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Semar small dam which is located in Mlatirejo village of Rembang Regency is built on Serojeh River with 10.62 km2 of watershed.. The function of Semar small dam is to fill the needs of raw water and irrigation water requirement. Semar small dam was is designed with 240.449 m3 of water capacity in +67 elevations. The effective volume of Semar small dam is 137.385 m3 which provides the needs of raw water and irrigation of them are 0.002 m3/sec and 0.08 m3/sec. This spillway is designed to reduce the flood of reissue 50 years period of 121.091 m3/sec into 43.47m3/sec. The small dam was a homogeneous soil with its 15 meter in height and 158 meter in length. This project implementation is scheduled for 28 weeks with a budget plan of Rp 8.469.864.600,00.